Subdosagens de Bacillus thuringiensis em Plutella xylostella (lepidoptera: Plutellidae) e Trichogramma pretiosum (hymenoptera: Trichogrammatidae) - de Bortoli, Sergio Antonio [UNESP]; Vacari, Alessandra Marieli [UNESP]; de Magalhães, Gustavo Oliveira [UNESP]; Dibelli, Wanderlei [UNESP]; de Bortoli, Caroline Placidi [UNESP]; Alves, Murilo Petrini [UNESP] (My University, 2012)
The aim of this paper was to evaluate the biological aspects of Plutella xylostella and Trichogramma pretiosum in eggs of the F2 generation of P. xylostella under the influence of Bacillus thuringiensis in laboratory conditions. The experiment was conducted in the Laboratório de Biologia and Criação de Insetos of Faculdade de Ciências Agrárias e Veterinárias de Jaboticabal - UNESP reen collars contaminated with strains and commercial product based on B. thuringiensis in the laboratory. The eggs obtained from the F2 generation of P. xylostella evaluated the biological parameters of T. pretiosum. It was observed that some biological characteristics of P. xylostella showed changes by the treatment with B. thuringiensis. The viability of the larvae and pupae stages, pupae weight were the biological parameters more influenced by treatments, with values significantly reduced when compared to control. However, the larvae length and pupae stages and sex ratio were similar in all treatments, with no significant biological variations. Thus, this bacterium isolated from this behavior may provide greater exposure of larvae to other natural enemies as well as generation of adults less viable, which makes them potential programs in pest control, since the interaction of the methods of control is one of the main ways to enhance the biological control of insect pests. It was observed sublethal effects on P. xylostella biology, and B. thuringiensis negative influence on the parasitism capacity and emergency of T. pretiosum.
Subdosages of Bacillus thuringiensis on Plutella xylostella) (lepepidoptera: Plutellidae) and Trichogramma pretiosum (hymenoptera: Trichogrammatidae)
Keywords: Diamondback moth; Entomopathogenous; Microbial control